Applying attachment theory to link family of origin violence history to cyber dating abuse among college students - Basting, Evan J. (Journal of family violence, 2023)
Purpose: Despite family of origin violence (FOV) exposure being consistently related to traditional forms of dating abuse (DA) perpetration and victimization, few studies have extended this association to cyber DA. As attachment insecurity is commonly linked to FOV exposure and DA, we examined whether attachment anxiety and attachment avoidance mediated the relation between FOV (i.e., experiencing parent-to-child aggression, witnessing interparental aggression) and cyber DA perpetration and victimization forms (i.e., direct cyber aggression, cyber monitoring/controlling, cyber sexual DA). Methods: We tested these associations using a crosssectional design with 584 college students. Results: Parent-to-child aggression was indirectly related to all forms of cyber DA perpetration and victimization through attachment anxiety. Attachment avoidance was unrelated to both forms of FOV; however, it was directly related to increased direct cyber aggression victimization, increased cyber sexual DA victimization, and decreased cyber monitoring/controlling perpetration. Findings suggested that those with a history of experiencing parent-to-child aggression may develop an anxious attachment style and perpetrate cyber DA to relieve distress associated with physical distance from their romantic partners. Additionally, people with avoidant attachment styles may be less apt to perpetrate cyber DA due to comfort with physical distance from romantic partners. Conclusion: These findings extended the intergenerational transmission of violence theory of DA etiology from in-person DA to cyber DA perpetration and victimization using an attachment theory framework. Cyber DA prevention research should explore interventions that reduce attachment insecurity, particularly among individuals with histories of parent-to-child aggression.